(untitled) (Bangladesh Journal of Botany, 2008)
A taxonomic account of eight species of pleurocarpous mosses from different localities of Bangladesh has been made. These are new addition to the pleurocarpous moss flora reported earlier. Key words : Pleurocarpous mosses, Hypnobryales, Sematophyllaceae, Bangladesh doi:10.3329/bjb.v36i1.1551 Bangladesh J. Bot. 36(1): 69-80, 2007 (June)